решите уравнение

(x-10)^2+(x+9)^2=2x^2

(x-5)^2+(x+4)^2=2x^2

x^2-3x-40=0

x^2+7x+6=0

x^2+6x+9=0

x^2+3x-54=0

1

Ответы и объяснения

2013-02-08T07:22:59+00:00

(x-10)^2+(x+9)^2=2x^2

x^2-20x+100+x^2+18x+81-2x^2=0

-2x+181=0

x=181/2=90,5

 

(x-5)^2+(x+4)^2=2x^2

x^2-10x+25+x^2+8x+16-2x^2=0

-2x+41=0

x=41/2=20,5

 

x^2-3x-40=0

D=9+160=169

x1=(3+13)/2=8

x2=(3-13)/2=-5

 

x^2+7x+6=0

D=49-24=25

x1=(-7+5)/2=-1

x2=(-7-5)/2=-6

 

x^2+6x+9=0

D=36-36=0

x=-6/2=-3

 

x^2+3x-54=0

D=9+4*54=225

x1=(-3+15)/2=6

x2=(-3-15)/2=-9